POLA HIDUP DENGAN KEJADIAN OBESITAS: LITERATURE REVIEW - Made Mahaguna Putra; Ni Nyoman Intan Saraswati; Ni Made Raningsih (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Obesity is an abnormal condition characterized by an excessive increase in body fat, generally deposited in the subcutaneous tissue, around the organs, and sometimes infiltrated into the organs. Obesity occurs due to changes in lifestyle, for example, drinking a lot, smoking habits, consuming lots of fatty foods, consuming fast food (fast food) a lot, and low physical activity. The main factors causing central obesity are increased food intake and decreased energy expenditure. Physical activity is also associated with central obesity. It is known that regular physical exercise can lead to a significant decrease in body fat tissue. This is because physical exercise can increase fat-free tissue mass and reduce fat tissue mass.